Identification of sisters separate (ssep), a gene required for meiotic centromere cohesion in Drosophila melanogaster. - Hewitt, S.T.; Pellizzari, S.; Thornton, S.; Ward, H.S.; Hylton, C.A.; Keat, A.; Shore, C.; Onuzulike, Y.; Giri, B.K.; Tomkiel Dean, J.E. (Genetics, 2025)
Cohesins regulate attachment between sister chromatids in both mitosis and meiosis. In Drosophila, two complexes of cohesins have been identified that have been proposed to differentially affect arm cohesion and centromere cohesion. We describe sisters separate (ssep), a newly identified gene required for meiotic sister chromatid cohesion. We demonstrate that ssep corresponds to CG30383, a previously uncharacterized gene. Mutations in ssep affect both sexes, and we show in males cause early separation of sister chromatids in meiosis I leading to nondisjunction of both sex chromosomes and autosomes. Effects of mutations in ssep and the centromeric cohesin sisters unbound are not additive, consistent with both genes acting in the same pathway. Sister centromeres separate precociously in ssep mutants during mid prophase I and show a pattern of nonrandom segregation. This nonrandom segregation is resolved by a mutation in mod(mdg4) in meiosis, a homolog conjunction complex protein. A bam-GAL4 driven mcherry-tagged ssep+ transgene rescues the NDJ and colocalizes with the Centromere IDentifier protein at centromeres throughout meiosis until anaphase II. Centromere localization is not detected when Ssep is expressed in spermatocytes after mid-prophase I, suggesting that loading is required earlier in meiosis and that there is no detectable turnover. Expression of a mutated form of Ssep lacking a putative conserved Separase cleavage site shows reduced centromere localization but still largely rescues the segregation defect. Ssep localization to centromeres is dependent on both sisters unbound and orientation disruptor. Together, these observations suggest that Ssep is essential for sister chromatid cohesion and is a part of the Sisters unbound/Sisters on the loose/Orientation disruptor centromeric cohesin complex.